The African Economic Partnership Agreements with the EU: Reflections inspired by the case of the East African Community - Jaime De Melo; Julie Regolo (Journal of African Trade, 2014)
This paper appraises the likely effects of the Economic Partnership Agreement (EPA) between the East African Community (EAC) and the European Union (EU). Customs data are used to estimate the revenue and welfare effects of an EPA with and without an exception list. Revenue and welfare effects are rather small. The paper then discusses the benefits that would have occurred had the EAC-EU protocol on rules of origin been simplified and made more compatible with the multilateral trading system. An inclusion of services would have also helped achieve the objective of increased competitiveness in goods trade, while the time table for tariff reduction in the EAC should have been shorter. The paper suggests in closing that the present appraisal is applicable also to the other African EPAs.
Keywords: F1; F4; O5; 330; Preferences; Regional integration; EPA